2021
DOI: 10.1101/2021.02.08.430280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SALTS – SURFR (sncRNA) And LAGOOn (lncRNA) Transcriptomics Suite

Abstract: The widespread utilization of high-throughput sequencing technologies has unequivocally demonstrated that eukaryotic transcriptomes consist primarily (>98%) of non-coding RNA (ncRNA) transcripts significantly more diverse than their protein-coding counterparts. ncRNAs are typically divided into two categories based on their length. (1) ncRNAs less than 200 nucleotides (nt) long are referred as small non-coding RNAs (sncRNAs) and include microRNAs (miRNAs), piwi-interacting RNAs (piRNAs), small nucleolar RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 74 publications
(129 reference statements)
0
11
0
Order By: Relevance
“…Therefore, in light of having found that tRNA-Thr-CGT-1-1, 44-73 tRF intracellular sequestration improves P22 infectivity, we next explored the potential role of tRNA-Thr-CGT-1-1, 44-73 tRF in OMV-mediated P22 restriction. SURFr 30,31 analysis of available S. Typhimurium OMV RNA-sequencing data (SRR6843039) 35 and qRT-PCR of our own OMV RNA isolates both confirm the presence of tRNA-Thr-CGT-1-1, 44-73 tRF within S. Typhimurium OMVs. What's more, we find tRNA-Thr-CGT-1-1, 44-73 tRF levels are ~3.5x higher in OMV RNA isolates than in total cellular RNA (Figure 3A).…”
Section: Smentioning
confidence: 54%
See 3 more Smart Citations
“…Therefore, in light of having found that tRNA-Thr-CGT-1-1, 44-73 tRF intracellular sequestration improves P22 infectivity, we next explored the potential role of tRNA-Thr-CGT-1-1, 44-73 tRF in OMV-mediated P22 restriction. SURFr 30,31 analysis of available S. Typhimurium OMV RNA-sequencing data (SRR6843039) 35 and qRT-PCR of our own OMV RNA isolates both confirm the presence of tRNA-Thr-CGT-1-1, 44-73 tRF within S. Typhimurium OMVs. What's more, we find tRNA-Thr-CGT-1-1, 44-73 tRF levels are ~3.5x higher in OMV RNA isolates than in total cellular RNA (Figure 3A).…”
Section: Smentioning
confidence: 54%
“…SRA IDs corresponding to bacterial small RNA-seq datasets were obtained from the NCBI SRA database 45 and entered directly into SURFr, a real-time NGS data analytic tool to identify and analyze ncRNA-derived RNAs, for analysis after selecting the desired bacterial species 30,31 . Filter was set to "tRNA" only, and all tables, reports, and images downloaded.…”
Section: Surfr Trf Annotation and Identification Of Phage Complementaritiesmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, we recently screened 12 preexisting small RNA seq datasets: six generated by our group 27 and six by others 28,29 for the presence of recurrent, speci cally excised tRFs. Through employing a novel RNA-seq analysis platform designed to annotate fragments excised from longer noncoding RNAs, (SURFr) 30,31 , we have successfully identi ed 31 recurrent, relatively abundant tRFs expressed by S. Typhimurium. These tRFs average 26.7 nt in length ranging between 19 nt for the shortest (tRNA-Pro-TGG-1-1, 49-75) and 38 nt for the longest (tRNA-fMet-CAT-2-1, 33-70).…”
Section: Resultsmentioning
confidence: 99%